Násilí na pracovišti a jeho prevence. - Uhrová, Aneta (Univerzita Pardubice, 2024)
The final thesis deals with workplace violence from the perspective of general nurses. The main objective of this thesis is to determine the extent and forms in which general nurses in an anonymous hospital in the Vysočina Region have encountered workplace violence. The text is divided into theoretical and practical parts. The theoretical part focuses on violence, particularly workplace violence, its impact on human health, violence in healthcare facilities, prevention and its resolution. The practical part includes the results of a questionnaire survey aimed at general nurses in a selected hospital. The questionnaire consists of three groups of questions - the first one focuses on demographic characteristics, the second includes the Negative Acts Questionnaire (NAQ-R), and the third is aimed at identifying the perpetrators of workplace violence. The data are processed using descriptive statistical methods, followed by testing with relevant statistical tests.
Workplace violence and its prevention.
Keywords: násilí; všeobecné sestry; mobbing; bossing; prevence; zdravotnická zařízení; violence; general nurses; mobbing; bossing; prevention; medical facilities